Is the Esophagus Spared during Pulsed Field Ablation? Early Histopathology & In Vivo Esophageal Retraction - Nies, Moritz; Koruth, Jacob S; Mlček, Mikuláš; Petru, Jan; Tibenská, Veronika C; Watanabe, Keita; Královec, Štepán; Hala, Pavel; Tejkl, Leoš; Neuzil, Petr; Reddy, Vivek Y (Heart rhythm, 2025)
BACKGROUND: Preclinical studies of pulsed field ablation (PFA) have demonstrated an absence of esophageal lesions. However, esophageal assessments are typically performed weeks after PFA, precluding an understanding of acute effects. OBJECTIVES: To understand the mechanism of esophageal safety with PFA, using preclinical and clinical assessments. METHODS: In 6 swine (early, n=4; late, n=2) under anesthesia and paralysis, the esophagus was manually displaced toward the inferior vena cava (IVC) using a balloon catheter. From the IVC, a pentaspline PFA catheter delivered 4 stacked applications at 4-7 sites. Animals were sacrificed either early (1 day) or late (14 days), followed by pathological assessment. PFA's mechanical effect on the esophagus was determined in other preclinical and clinical studies (with or without paralytics) by contrast fluoroscopy during left atrial PFA. RESULTS: After 1 day, 3 of 4 animals demonstrated esophageal lesions, measuring 13.3±8.5 mm long, 6.3±5.9 mm wide, and 2.3±0.6 mm deep. All lesions were non-transmural, with myocyte degeneration and leucocyte infiltration on histology; the mucosa and blood vessels were spared. Conversely, the 14-day cohort exhibited no lesions upon gross necropsy or histology. During atrial PFA using various catheters, waveforms and manufacturers, esophageal contraction universally occurred such that it functionally retracted away from the point of ablation. CONCLUSIONS: The pentaspline PFA catheter creates acute non-transmural esophageal lesions that resolve by 14 days. The "functional sparing" of the esophagus during PFA is not due to absolute esophageal sparing, but rather to a combination of favorable tissue healing and, likely, some degree of esophageal contraction/retraction.
Keywords: preclinical; pulsed field ablation; esophagus; electroporation; catheter ablation